The neoarchean uyea gneiss complex, shetland: An onshore fragment of the rae craton on the European plate - Kinny, Pete; Strachan, R.A.; Fowler, M.; Clark, Chris; Davis, S.; Jahn, I.; Taylor, Richard; Holdsworth, R.E.; Dempsey, E. (GEOLOGICAL SOC PUBL HOUSE, 2018)
© 2019 The Author(s). Published by The Geological Society of London. All rights reserved. A tract of amphibolite-facies granitic gneisses and metagabbros in northern Shetland, UK, is here named the Uyea Gneiss Complex. Zircon U–Pb dating indicates emplacement of the igneous protoliths of the complex c. 2746–2726 Ma, at a later time than most of the Archean protoliths of the Lewisian Gneiss Complex of mainland Scotland. Calc-alkaline geochemistry of the Uyea Gneiss Complex indicates arc-affinity and a strong genetic kinship among the mafic and felsic components. Zircon Hf compositions suggest an enriched mantle source and limited interaction with older crust during emplacement. Ductile fabrics developed soon after emplacement, with zircon rims at c. 2710 Ma, but there was little further deformation until Caledonian reworking east of the Uyea Shear Zone. There is no evidence for the Paleoproterozoic reworking that dominates large tracts of the Lewisian Gneiss Complex and of the Nagssugtoqidian Orogen of East Greenland. The more northerly location of the Uyea Gneiss Complex and extensive offshore basement of similar age implies that, prior to the opening of the North Atlantic Ocean, these rocks were contiguous with the Archean Rae Craton.